Structural-phase state of R6M5 high-speed steel after thermal processing - Rakhadilov, B. K.; Karipbayeva, G. S.; Skakov, M. K.; Manapbayeva, A. B. (Recent Contributions to Physics, 2014)
In this work by scanning electron microscopy, EBSD-analysis and X-ray structure analysis investigate microstructure, morphology, elemental composition, phase composition and crystal structure of R6M5 steelafter standard thermal treatment. It is shown that the microstructure of the steel R6M5 after hardening and three-time tempering consists of tempered martensite and solid carbide M6C-type and MC spherical shape. Volume fraction of carbides and their distributiondefined. The main carbides in the study of steel after heat treatment – M6C and MS carbides who have a complex FCC lattice and space group Fd3m has established by X-ray structural analysis method. Carbides are homogeneous and single crystal. ESBD-analysis method with the support of X-ray structural analysis has established that the bright carbides spherical shape M6C correspond to the composition Fe3W3C, and gray carbides spherical shape MC correspond to the composition of the VC.